The Physiatry Workforce in 2019 and Beyond, Part 1: Results From a Cross-sectional Survey. (13th September 2021) - Forte, Gaetano J.; Langelier, Margaret; Wang, Shen; Dall, Timothy M.; Reynolds, Ryan L.; Chakrabarti, Ritashree; Whyte, John; Ankam, Nethra Sridhara; Annaswamy, Thiru M.; Fredericson, Michael; Jain, Nitin B.; Karimi, Danielle Perret; et al.
Abstract : Objective: The aim of the study was to describe the current physiatrist workforce in the United States. Design: An online, cross-sectional survey of board-certified physiatrists in 2019 ( N = 616 completed, 30.1% response) collected information about demographic and practice characteristics, including age, sex, practice area, practice setting, hours worked, patient characteristics, staffing, and work responsibilities. Physiatrists were stratified by substantive practice patterns using a cluster analysis approach. Survey responses were arrayed across the practice patterns and differences noted. Results: The practice patterns identified included musculoskeletal/pain medicine, general/neurological rehabilitation, academic practice, pediatric rehabilitation, orthopedic/complex conditions rehabilitation, and disability/occupational rehabilitation. Many differences were observed across these practice patterns. Notably, primary practice setting and the extent and ways in which other healthcare staff are used in physiatry practices differed across practice patterns. Physiatrists working in musculoskeletal/pain medicine and disability/occupational rehabilitation were least likely to work with nurse practitioners and physician assistants. Physiatrists working in academic practice, general/neurological rehabilitation, and pediatric rehabilitation were most likely to have primary practice settings in hospitals. Conclusions: Physiatry is an evolving medical specialty affected by many of the same trends as other medical specialties. The results of this survey can inform policy discussions and further research on the effects of these trends on physiatrists and physiatry practice in the future.